2023
DOI: 10.3390/buildings13030742
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Indoor Air Quality and Ventilation to Limit Aerosol Dispersion—Literature Review

Abstract: The COVID-19 pandemic highlighted the importance of indoor air quality (IAQ) and ventilation, which researchers have been warning about for years. During the pandemic, researchers studied several indicators using different approaches to assess IAQ and diverse ventilation systems in indoor spaces. To provide an overview of these indicators and approaches in the case of airborne transmission through aerosols, we conducted a literature review, which covered studies both from before and during the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…On the other hand, indoor air quality indices lack the standardization seen in ambient air quality measures. Efforts are frequently tailored to specific building types, occupancy rates, and local pathogens [57][58][59][60]. Parameter selection for these indices is often contingent upon pollutant concentrations relevant to the building's activities or specific local pollutants.…”
Section: Air Quality Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, indoor air quality indices lack the standardization seen in ambient air quality measures. Efforts are frequently tailored to specific building types, occupancy rates, and local pathogens [57][58][59][60]. Parameter selection for these indices is often contingent upon pollutant concentrations relevant to the building's activities or specific local pollutants.…”
Section: Air Quality Indexmentioning
confidence: 99%
“…Parameter selection for these indices is often contingent upon pollutant concentrations relevant to the building's activities or specific local pollutants. Moreover, such IAQ indices are not restricted to IAQ parameters alone [59]. A recent example from the literature presents an Indoor Environmental Quality index, which includes thermal comfort, acoustic comfort, and illumination levels [58].…”
Section: Air Quality Indexmentioning
confidence: 99%
“…The worldwide pandemic has raised the interested in CO 2 traffic lights to stimulated window ventilation. Increased ventilation reduces the aerosol content in the room air [25]. Aerosol contamination was found to be the major path of infection in rooms occupied by multiple persons.…”
Section: Individual Measuresmentioning
confidence: 99%
“…The recent SARS-CoV-2 (COVID-19) has drawn much attention to this issue due to its devastating health, social, and economic impacts worldwide. Before the COVID-19 pandemic, several studies showed the relationship between airborne transmission and indoor ventilation [17]. The emergence of Severe Acute Respiratory Syndrome (SARS) outbreak in 2002-03, the H1N1 influenza epidemic in 2011 and the threat of a different influenza pandemic, the Middle East Respiratory Syndrome (MERS) outbreak in 2012, the global prevalence of tuberculosis serve as timely reminders of the substantial risk posed to human health by airborne infectious diseases [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…In indoor spaces, there are many potential sites for spreading pathogens, including sick/infected persons, contaminated indoor air, and the threat of recirculated contaminated air through the heating, ventilation, and air conditioning (HVAC) systems. Different studies indicate HVAC, fans, humidifiers, etc., as the major sources of propagation and spread of microorganisms in indoor buildings [5], [11], [17], [22].…”
Section: Introductionmentioning
confidence: 99%